Determinants of technical efficiency of coffee production in Jimma Zone, Southwest Ethiopia - Negese Tamirat; Sanait Tadele (Heliyon, 2023)
Agriculture has been and continues to assume center stage in the economic policy of Ethiopia. Coffee is one of the most vital sources of income for many coffee growers and continues to be still the leading export commodity in the national economy of the country. Despite the economic use, the productivity and quality of the coffee are unsatisfactory. The adoption of coffee yield-enhancing technical efficiency is key to improving coffee productivity and quality. Therefore, this study aims to investigate determinants that influence the technical efficiency of coffee production in Jimma Zone, Southwest Ethiopia. The primary data was collected among 398 coffee growers in research locations during the 2020/21 season. Descriptive statistics and econometric methods were developed for the data analysis. The estimated average value of technical, allocative, and economic efficiencies was 82.63%, 78.35%, and 74.65% respectively, which shows the existence of inefficiency in coffee production in the study area. The findings of OLS regression indicated that technical inefficiency is affected by age, sex, education status, landholding, livestock holding, credit uses, the extension uses, off-farm activity, land ownerships, seed, and variety of coffee planted. Coffee yield technical efficiency was associated with a significantly higher coffee yield and per capita annual income of coffee cultivators. Concerned bodies should give important attention to coffee yield enhancing technical efficiency which is base for improving production. The summary of this coffee production technical efficiency by policymakers and plan designers could bring better enhancement to the coffee cultivator in the study area.